Corrective Feedback in eTandem Learning: A Socially Shared Regulation Perspective - Tam, Chui Ling (Journal of Foreign Language Teaching and Learning, 2026)
Background: While tandem learning has gained increasing popularity, limited attention has been paid to how corrective feedback functions as a mechanism of socially shared regulation. Objective:This study, therefore, examines how learners in eTandem contexts negotiate corrective feedback practices during the provision and reception of feedback. This study adopted a qualitative exploratory design. Methods: Eleven participants with prior eTandem experience responded to an open-ended questionnaire, and the data were analyzed using thematic analysis. Findings: The findings indicate that, as providers, learners tended to provide corrective feedback based on their own beliefs about appropriate practices, whereas, as recipients, they generally accepted corrective feedback passively without explicitly negotiating their expectations. Despite this limited negotiation, most participants reported satisfaction with the feedback process. These findings suggest that although co-regulatory processes were present, they rarely developed into socially shared regulation. Conclusion: This study contributes to a deeper understanding of eTandem learning as a collaborative regulatory process and highlights the need to enhance learners' capacity for socially shared regulation.